Analysis of the Marxist Theory on the Abolition of State: Its Implication to Nigeria Educational System - Ifeakor, Chinedu; Odo, Anselm Ikenna (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Certain factors necessitated man’s thinking especially, if it focuses on alteration of their desire and wants. It is on this, that some years back some philosophers propounded a theory which stated thus: the abolition of a state. The Marxist theory on the abolition of the state asserted that society’s classes are the cause of struggle and that society should have no classes. An example of Marxism is replacing private ownership with cooperative ownership. The researchers of this work will adopt an analytic method in order to find out if the theory should be a paradigm in the Nigeria education or not.